Systematic Review and Meta-Analysis of the Medium- and Long-Term Outcomes of the Boston Type 1 Keratoprosthesis. Issue 11 (November 2019) - Priddy, Jack; Bardan, Ahmed Shalaby; Tawfik, Hadeel Sherif; Liu, Christopher
Abstract : Purpose: The Boston type 1 keratoprosthesis (KPro), used in patients with high risk of corneal graft failure, is increasingly being used. However, the medium- to long-term outcomes are currently unclear. We analyzed the medium- (2–5 years) and long-term (>5 years) efficacy and safety of the Boston type 1 KPro in terms of visual outcomes, device retention, and postoperative complications. Methods: We last searched electronic databases (Ovid MEDLINE, Ovid MEDLINE In-Process and Other Non-Indexed Citations, Ovid MEDLINE Daily, Ovid MEDLINE Epub Ahead of Print, EMBASE, and CENTRAL) on March 31, 2018. Visual outcomes and device retention at 2 and 5 years, alongside postoperative complications, were primary outcome measures. Results: We identified 407 articles. Thirty studies were included in this systematic review and meta-analysis. The combined proportion of eyes with ≥6/60 vision was 62% at 2 years and 51% at 5 years. The combined retention rate was 88% at 2 years and 74% at 5 years. Retroprosthetic membrane (36.6%) and glaucoma (39.3%) were found to be the most common long-term complications. Very few studies showed visual outcomes or retention rates at 5 years, with results sparse and collectively not meaningful because of small patient numbers and ambiguous reporting of follow-up times. Conclusions: The 2-year results indicate that there is a place for the Boston type 1 KPro in the management of corneal blindness. However, there is scarce evidence regarding its medium- and long-term efficacy and safety. The high rate of reported complications necessitates strict patient selection and stringent follow-up. Abstract : Supplemental Digital Content is Available in the Text.